2018
DOI: 10.1155/2018/6513682
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Rotavirus A in Nigeria: Molecular Diversity and Current Insights

Abstract: Rotavirus induced acute gastroenteritis AGE has been a major disease burden in Nigeria, since it was first reported in 1985. Prevalence rates have increased with severe public health consequences particularly among children. The vaccine Rotarix® has been introduced and is commercially available in Nigeria. However routine rotavirus vaccination is yet to be introduced into the National Immunization Program. Molecular epidemiology of rotavirus in Nigeria has shown the presence of various genotypes, with genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Molecular epidemiology has identified the widespread circulation of various genotypes of rotavirus in Africa, the globally prevalent genotypes G1P [8], G3P [4] have been reported in various African countries [7, 8, 9, 10, 11]. However these globally prevalent genotypes are being replaced by more recent genotypes such as G9P [8], G8P [4], G12P [6], G12P [8], as previously reported [12].…”
Section: Introductionmentioning
confidence: 71%
“…Molecular epidemiology has identified the widespread circulation of various genotypes of rotavirus in Africa, the globally prevalent genotypes G1P [8], G3P [4] have been reported in various African countries [7, 8, 9, 10, 11]. However these globally prevalent genotypes are being replaced by more recent genotypes such as G9P [8], G8P [4], G12P [6], G12P [8], as previously reported [12].…”
Section: Introductionmentioning
confidence: 71%
“…Furthermore, administration of these vaccines in humans has yielded some positive results as revealed in a few studies that reported reduction in human exposure to rotavirus in some LMICs (Armah et al., ; Bar‐Zeev et al., ; Schwartz et al., ). Notwithstanding, rotavirus vaccines are not yet widely available in some LMICs (Motayo, Faneye, & Adeniji, ; Sindhu, Babji, & Ganesan, ). Contrary to the case of rotavirus, development of norovirus vaccines is still ongoing (Hallowell, Parashar, & Hall, ; Riddle, Chen, Kirkwood, & MacLennan, ), and thus a licensed norovirus vaccine is currently unavailable (Huys, Grau, & Karst, ).…”
Section: Viruses In Rtes From Lmicsmentioning
confidence: 99%
“…G12P [8] was also found to be the most frequent genotype circulating in Mozambique in 2011 in Gaza Province, while G12P[6] was most frequently detected in Maputo Province in 2012 and 2013 in the pre-vaccine introduction period [16,17]. Similar reports have shown G12P [8] as an important emerging combination worldwide, which reached a higher proportion than other common combinations [33,34]. By contrast, countries such as Ghana and Burkina Faso reported the circulation of G12P [8] after rotavirus vaccine introduction into their immunization programs [35,36].…”
Section: Discussionmentioning
confidence: 82%